Project-Based Science-Physics E-Book to Train Student Creativity - Kurniawan Arizona; Ramdhani Sucilestari; Baiq Mutiara Alika Nirmala; Lalu Ahmad Didik Meiliyadi (Postgraduate, University of Mataram, 2025)
This study aims to develop a project-based Science-Physics E-Book to enhance student creativity in the Madrasah Ibtidaiyah Teacher Education (PGMI) program at the State Islamic University (UIN) of Mataram. The need for innovative learning resources to improve understanding of science and physics concepts, as well as foster 21st-century skills, particularly creativity, in prospective primary school teachers, forms the basis of this research. The method used is Research and Development (R&D) with the ADDIE model. In the analysis stage, learning needs and student characteristics were assessed through interviews, questionnaires, and document analysis. The design phase included developing an E-Book framework with interactive elements. The content was enriched with multimedia and integrated into a project-based learning approach. Limited and extensive trials were conducted with PGMI UIN Mataram students. Formative and summative evaluations assessed the effectiveness of the e-book in fostering student creativity (p < 0.05). Results indicated that the e-book successfully enhanced creativity, as reflected in higher creativity scores and positive feedback from students and lecturers. The novelty of this research lies in the creation of an interactive, project-based E-Book, a first for PGMI UIN Mataram, contributing to the advancement of digital learning resources for primary school teacher education.